Continuous Activity Monitoring During Concurrent Chemoradiotherapy - Ohri, Nitin; Kabarriti, Rafi; Bodner, William R.; Mehta, Keyur J.; Shankar, Viswanathan; Halmos, Balazs; Haigentz, Missak; Rapkin, Bruce; Guha, Chandan; Kalnicki, Shalom; Garg, Madhur (International journal of radiation oncology, biology, physics, 2017)
To perform a prospective trial testing the feasibility and utility of acquiring activity data as a measure of health status during concurrent chemoradiotherapy. Ambulatory patients who were planned for treatment with concurrent chemoradiotherapy with curative intent for cancers of the head and neck, lung, or gastrointestinal tract were provided with activity monitors before treatment initiation. Patients were asked to wear the devices continuously throughout the radiation therapy course. Step count data were downloaded weekly during radiation therapy and 2 and 4 weeks after radiation therapy completion. The primary objective was to demonstrate feasibility, defined as collection of step counts for 80% of the days during study subjects' radiation therapy courses. Secondary objectives included establishing step count as a dynamic predictor of unplanned hospitalization risk. Thirty-eight enrolled patients were treated with concurrent chemoradiotherapy. Primary diagnoses included head and neck cancer (n=11), lung cancer (n=13), and a variety of gastrointestinal cancers (n=14). Step data were collected for 1524 of 1613 days (94%) during patients' radiation therapy courses. Fourteen patients were hospitalized during radiation therapy or within 4 weeks of radiation therapy completion. Cox regression modeling demonstrated a significant association between recent step counts (3-day average) and hospitalization risk, with a 38% reduction in the risk of hospitalization for every 1000 steps taken each day (hazard ratio 0.62, 95% confidence interval 0.46-0.83, P=.002). Inferior quality of life scores and impaired performance status were not associated with increased hospitalization risk. Continuous activity monitoring during concurrent chemoradiotherapy is feasible and well-tolerated. Step counts may serve as powerful, objective, and dynamic indicators of hospitalization risk.